LOX1-mediated supramolecular self-assembly nanomedicine for microsatellite-stable colorectal cancer towards reactivating anti-tumor immunity - Wei, Xin; Guo, Yuyan; Lei, Jianyuan; Chen, Na (Frontiers in Immunology, 2025)
IntroductionMicrosatellite stable colorectal cancer (MSS-CRC) is referred to as an immune desert-type tumor. Emerging studies have demonstrated that inhibition of the Wnt/β-catenin pathway can enhance the anti-tumor immune response. This research focuses on synthesizing the human serum albumin (HSA) -based Wnt inhibitor GHSACA and assessing its internalization pathway and therapeutic effectiveness in conjunction with PD-1 antibody for treating MSS-CRC.MethodsGlucosamine was covalently conjugated to HSA via EDC/NHS activation to generate GHSA, which was subsequently coupled with carnosic acid (CA) -Wnt pathway inhibitor, to synthesize GHSACA. For in vitro studies, LOX1- and CD44- deficient MC38 and CT26 colon cancer cell lines, validated by RT-qPCR, were used to investigate the cellular uptake mechanism and macropinocytic activity of GHSACA using flow cytometry. The effectiveness of GHSACA in targeting tumors in vivo was assessed in CT26 tumor-bearing BALB/c mice via fluorescence imaging. Therapeutic efficacy was assessed in MSS-CRC patient-derived xenograft (PDX).ResultsRT-qPCR confirmed efficient knockdown of LOX1 and CD44 in both MC38 and CT26 cell lines. Cellular uptake assay demonstrated that GHSACA internalization is predominantly mediated by the LOX1-dependent macropinocytosis pathway. In vivo fluorescence imaging revealed sustained accumulation of GHSACA in tumor and rapid clearance from normal organs. In the PDX model, GHSACA monotherapy significantly suppressed tumor growth (TGI = 59.3%). The combination with PD-1 antibody (G&P group) resulted in further enhancement of antitumor efficacy (TGI = 87.9%). TUNEL assays showed the most pronounced induction of tumor cell apoptosis in the G&P group. Immunohistochemical analysis demonstrated that GHSACA suppressed the Wnt/β-catenin signaling cascades, alongside with lower Ki67 expression. The G&P combination increased PD-L1 expression and significantly boosted Granzyme B-positive cytotoxic immune responses. Immunofluorescence double staining showed the highest infiltration of CD3+/CD8+ cytotoxic T lymphocytes of the G&P group, with a concurrent decrease in CD4+/CD25+ regulatory T cells. GHSACA was found to have favorable systemic biocompatibility and safety.DiscussionGHSACA achieves efficient targeted cellular internalization via a macropinocytosis pathway regulated by the LOX1 receptor rather than the CD44 receptor, simultaneously inhibiting the Wnt/β-catenin signaling while activating anti-tumor immune responses. It provides a highly promising translational therapeutic approach for overcoming immune resistance in MSS-CRC.